Infectiousness of Asymptomatic Meriones shawi, Reservoir Host of Leishmania major - Jovana Sadlova; Barbora Vojtkova; Tereza Lestinova; Tomas Becvar; Daniel Frynta; Kamal Eddine Benallal; Nalia Mekarnia; Zoubir Harrat; Petr Volf (Pathogens, 2023)
Leishmaniases are neglected diseases caused by protozoans of the genus Leishmania that threaten millions of people worldwide. Cutaneous leishmaniasis (CL) caused by L. major is a typical zoonosis transmitted by phlebotomine sand flies and maintained in rodent reservoirs. The female sand fly was assumed to become infected by feeding on the skin lesion of the host, and the relative contribution of asymptomatic individuals to disease transmission was unknown. In this study, we infected 32 Meriones shawi, North African reservoirs, with a natural dose of L. major obtained from the gut of infected sand flies. Skin manifestations appeared in 90% of the animals, and xenodiagnosis with the proven vector Phlebotomus papatasi showed transmissibility in 67% of the rodents, and 45% were repeatedly infectious to sand flies. Notably, the analysis of 113 xenodiagnostic trials with 2189 sand flies showed no significant difference in the transmissibility of animals in the asymptomatic and symptomatic periods; asymptomatic animals were infectious several weeks before the appearance of skin lesions and several months after their healing. These results clearly confirm that skin lesions are not a prerequisite for vector infection in CL and that asymptomatic animals are an essential source of L. major infection. These data are important for modeling the epidemiology of CL caused by L. major.